Pengaruh Kombinasi Pupuk N, P, K dan Kasgot yang Diperkaya Agen Hayati terhadap Hasil Tanaman Jagung Manis pada Inceptisol asal Jatinangor - Bawana, Saedi; Sofyan, Emma Trinurani; Salsabilla, Annisya; Septianugraha, Reza (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
The inefficiency of chemical fertilizers in crop production has encouraged the development of more sustainable and environmentally friendly alternatives. One of the approaches is through the useof organic fertilizers enriched with beneficial microorganisms. This study aimed to evaluate the effectof N, P, K fertilizers combination with kasgot (vermicompost derived from sewage sludge) enrichedwith biofertilizers on the yield of sweet corn (Zea mays L.) grown on Inceptisols. The experiment wasconducted from February to September 2024 at the Experimental Field of the Faculty of Agriculture,Universitas Padjadjaran, Jatinangor. A Randomized Complete Block Design was used, consisted ofeight treatments: one control (no fertilizer), one treatment with the recommended N, P, K dose, onetreatment with ¾ of the recommended dose of inorganic fertilizer, and and five treatments withvarious doses of kasgot enriched with biofertilizers and NPK fertilizers. Each treatment was replicatedthree times. The results showed that the combination of ¾ NPK dose and 1½ dose of enriched withbiofertilizers resulted in the best growth and yield performance. This treatment produced the highestear weight with husk (495.95 g), ear length (20.56 cm), and ear diameter (56.00 mm) compared toother treatments. The result suggested that the integrated application of biofertilizers and reduceddoses of chemical fertilizers can improve sweet corn yield while minimize the dependence on syntheticinputs, which promotes more sustainable and efficient agricultural practices.